Radioactive Music: The Eerie Agency of Hildur Guðnadóttir’s Music for the Television Series Chernobyl - Størvold Tore; Richardson John (University of Illinois Press, 2022)
The acclaimed television miniseries Chernobyl (2019) features an eerie soundtrack that musicalizes the silence of radioactivity. Hildur Guðnadóttir’s score is composed of field recordings from a nuclear power plant, treated and fitted together in ways that blur the lines between music and sound design. The immersive qualities of the soundtrack provide television audiences with new means of sensing the invisible ecological consequences of human activity. Størvold,